German Middle East and North Africa policy: Interests, strategies, options - Guido Steinberg (Stiftung Wissenschaft und Politik (SWP), 2009)
Germany has begun pursuing more active diplomacy in the Middle East and North Africa, although policy-makers still shy away from defining the country's interests there - especially for states and regions that have only recently come into the spotlight, like Iraq, the Arabian Peninsula and the Maghreb, and issues like migration, Islamist terrorism and energy. This study closes that gap by identifying Germany's objectives, interests and options in the region, examining the extent to which concepts and strategies have been developed, and exploring whether the identified approaches match up to the aims.Germany will only be able to acquire influence if it succeeds in developing concepts of its own and offering meaningful contributions. That presupposes a systematic discussion of the country's interests. The thread running through German policy in the region is all too often restricted to long-established priorities such as the Israeli-Arab conflict and Iran. Given the growing challenges confronting Germany in the region that is not enough
Keywords: 320